Association between composite dietary antioxidant index and cognitive function impairment among the US older adults: a cross-sectional study based on the NHANES 2011–2014 - Zhao, Cong; Pu, Meng; Wu, Chengji; Ding, Jiaqi; Guo, Jun; Zhang, Guangyun (Frontiers in Nutrition, 2024)
Background Cognitive function impairment (CFI) and the Composite Dietary Antioxidant Index (CDAI) were investigated in this study. Methods Participants from the 2011–2014 cycles of the National Health and Nutrition Examination Survey were chosen to assess cognitive function using the Consortium to Establish a Registry for Alzheimer’s Disease Word Learning Test, the Animal Fluency Test, and the Digit Symbol Substitution Test. Participants scored below the 25% percentile of any of the three tests were defined as having cognitive function impairment. 24-h recalls of diet were collected to calculate CDAI. Results 2,424 participants were included. The fully adjusted multivariate logistic regression model showed an increase of one CDAI unit reduced CFI risk by 5% (95% CI: 0.92 ~ 0.98, p = 0.004). When comparing individuals with the lowest CDAI in the first quartile (<−2.42), the adjusted odds ratio for CDAI and CFI were 0.81 (95% CI: 0.61 ~ 1.06, p = 0.125) in the second quartile, 0.69 (95% CI: 0.51 ~ 0.92, p = 0.012) in the third quartile, and 0.59 (95% CI: 0.43 ~ 0.82, p = 0.002) in the fourth quartile, respectively. Restricted cubic spline analysis revealed a steady negative linear correlation between CDAI and CFI, with a p-value for non-linearity of 0.122. Subgroup analysis did not reveal any significant interactions based on age, education level, family income, history of diabetes, hypertension, stroke, and depression. Conclusion CDAI was inversely associated with CFI in a large representative American population. Further longitudinal studies are needed for causal inference.